The Use of Deep Learning-Based Gesture Interactive Robot in the Treatment of Autistic Children Under Music Perception Education - Zhang, Yiyao; Zhang, Chao; Cheng, Lei; Qi, Mingwei (Frontiers in Psychology, 2022)
The purpose is to apply deep learning to music perception education. Music perception therapy for autistic children using gesture interactive robots based on the concept of educational psychology and deep learning technology is proposed. First, the experimental problems are defined and explained based on the relevant theories of pedagogy. Next, gesture interactive robots and music perception education classrooms are studied based on recurrent neural networks (RNN). Then, autistic children are treated by music perception, and an electroencephalogram (EEG) is used to collect children's music perception effect and disease diagnosis results. Due to significant advantages in signal feature extraction and classification, RNN is used to analyze the EEG of autistic children receiving different music perception treatments to improve classification accuracy. The experimental results are as follows. The analysis of EEG signals proves that different people have different perceptions of music, but this difference fluctuates in a certain range. The classification accuracy of the designed model is about 72% ~ 94%, and the average classification accuracy is about 85%. The model’s average accuracy of EEG classification of autistic children is 85%, and that of healthy children is 84%. The test results with similar models also prove the excellent performance of the design model. This exploration provides a reference for applying artificial intelligence technology in music perception education to diagnose and treat autistic children.